Analysis of the Effectiveness of Using Team-Based Quizzes to Improve Student Learning Outcomes in Informatics Subjects in Phase F10 Class of SMA Negeri 4 Surakarta - Efendi, Mohamad Danil; Dwi Maryono; Adi Waskito (Politeknik NEST, 2024)
This study analyzed the effectiveness of using team-based quizzes in improving student learning outcomes in Informatics subjects in Phase F10 classes at SMA Negeri 4 Surakarta. The research method used an experimental design with an experimental class that used team-based quizzes and a control class that used conventional methods. The results showed a significant increase in student learning outcomes in the experimental class compared to the control class. The average final score of the experimental class increased from 65 to 85, while the control class increased from 66 to 75. These findings suggest that team-based quizzing can increase active participation, cooperation, and understanding of the subject matter by students. This method also provides additional benefits in the development of social skills and cooperation. This study concludes that team-based quizzing is an effective learning method and can be widely applied in education.